Report of 2018 equine influenza outbreak in Chile - Moreira, Rubén; García, Alfonso; Ahumada, Carolyn; Badía, Catalina; Suárez, Paulina; Yangari, Betty; Aguayo, Carolina; Herrera, José; Espejo, Gabriela; Pinto, Enrique (Austral Journal of Veterinary Sciences, 2019)
The present study reports an outbreak of equine influenza (EI) occurred in Chile in January 2018, with cases spread along the country, from the Atacama to the Magallanes Region. The virus identified corresponded to the H3N8 subtype, affecting equines, donkeys, and mules. Clinical signs ranged from mild to severe, with a higher mortality rate in donkeys.